A bidirectional relationship between anxiety, depression and gastrointestinal symptoms in Parkinson's disease. (2021) - Jones, Jacob D.; Dominguez, Brandon; Bunch, Joseph; Uribe, Carmen; Valenzuela, Yenny; Jacobs, Jonathan P.
Highlights: Gastrointestinal (GI) and mood symptoms are common in Parkinson's disease. Depression and anxiety are bidirectional risk factors for GI distress. Association between GI and mood symptoms may reflect disrupted Gut-Brain axis. Abstract: Introduction: Anxiety, depression and gastrointestinal (GI) symptoms are common non-motor symptoms in Parkinson's disease (PD). Past studies provide evidence of a disrupted microbiome-gut-brain axis in PD, which is associated with certain motor and non-motor symptoms in PD. Additionally, there is evidence of a bidirectional association between mental health and gut health among individuals with GI disorders. The current study examined the bidirectional association between GI symptoms and anxiety/depression among individuals newly diagnosed with PD. Methods: We conducted a secondary data analysis of the Parkinson's Progression Markers Initiative. This included 487 individuals newly diagnosed with PD and followed for up to 5 years. Participants completed questionnaires of anxiety, depression and GI symptoms (Scales for Outcomes in Parkinson's Disease Autonomic; SCOPA-AUT) at each annual visit. Multilevel models examined the bidirectional-lagged relationship between GI symptoms and anxiety/depression. Results: Models provided evidence for a bidirectional relationship between GI symptoms and anxiety/depression. Specifically, more severe GI symptoms predicted more severe anxious/depressive symptoms within the same year and at the following year. There was also evidence of the inverse directionality, meaning that more severe anxiety/depression predicted more severe GI symptoms concurrently and in the following year. Discussion: Findings provide preliminary evidence for a cyclical relationship among gut health and mental health in PD. Future studies are needed to examine if the microbiome-gut-brain axis plays a mechanistic role.